A fully automated measurement system for the characterization of micro thermoelectric devices near room temperature. (April 2023) - Tanwar, Amit; Lal, Swatchith; Kaur, Rajvinder; Padmanathan, N.; Dalton, Eric; Razeeb, Kafil M.
Highlights: A micro-thermoelectric device (µ-TED) characterisation system is developed based on ASTM standard. The system validation is performed based on the output performance of µ-TEDs. It can maintain a temperature gradient with an accuracy of less than ±0.1 K. This system can characterise both the power generation and cooling performances. Output performance of the devices showed an acceptable deviation of less than 4%. Abstract: In this work, we report the customized design and development of a fully automated measurement system to characterize the temperature-dependent properties of microscale thermoelectric devices. The featured system can characterize the devices up to a dimension of 8.79 × 8.79 mm 2 in an atmospheric environment. Commercially available bismuth telluride-based thermoelectric modules (both thermoelectric generator and thermoelectric cooler) are used to validate the feasibility and accuracy of the developed system. Their performance data is analysed and compared with the available manufacturer datasheet. The measured data from these devices are found to be in good agreement with the anticipated values and showed an acceptable deviation of less than 4% in the output performances. The developed setup is simple to operate and suitable for performance evaluation of both macro and micro-thermoelectric devices. The system accurately reproduces application conditions the module may be subjected to in a real-world environment.